Quantum dots induced interferon beta expression via TRIF-dependent signaling pathways by promoting endocytosis of TLR4. (17th February 2016) - Ho, Chia-Chi; Luo, Yueh-Hsia; Chuang, Tsung-Hsien; Lin, Pinpin
Abstract: Quantum dots (QDs) are nano-sized semiconductors. Previously, intratracheal instillation of QD705s induces persistent inflammation and remodeling in the mouse lung. Expression of interferon beta (IFN-β), involved in tissue remodeling, was induced in the mouse lung. The objective of this study was to understand the mechanism of QD705 induced interferon beta (IFN-β) expression. QD705-COOH and QD705-PEG increased IFN-β and IP-10 mRNA levels during day1 to 90 post-exposure in mouse lungs. QD705-COOH increased IFN-β expression via Toll/interleukin-1 receptor domain-containing adapter protein (TRIF) dependent Toll-like receptor (TLR) signaling pathways in macrophages RAW264.7. Silencing TRIF expression with siRNA or co-treatment with a TRIF inhibitor tremendously abolished QD705s-induced IFN-β expression. Co-treatment with a TLR4 inhibitor completely prevented IFN-β induction by QD705-COOH. QD705-COOH readily entered cells, and co-treatment with either inhibitors of endocytosis or intracellular TLRs prevented IFN-β induction. Thus, activation of the TRIF dependent TLRs pathway by promoting endocytosis of TLR4 is one of the mechanisms for immunomodulatory effects of nanoparticles.